Association of Binge Eating Behavior with Total and Abdominal Adipose Tissue in a Large Sample of Participants Starting a Weight Loss or Maintenance Program. (17th November 2018) - Leone, Alessandro; Vignati, Laila; Battezzati, Alberto; De Amicis, Ramona; Ponissi, Veronica; Beggio, Valentina; Bedogni, Giorgio; Vanzulli, Angelo; Bertoli, Simona
ABSTRACT: Objective: It is not clear whether binge eating (BE) behavior is associated with body composition independently of body mass index (BMI). Our aim has been to evaluate the BMI-independent contribution of BE severity and BE status on the total amount of fat mass and abdominal fat distribution in a large sample of participants. Method: We performed a cross-sectional study among 8524 participants followed at a nutritional center. BMI and waist circumference (WC) were measured, body fat (BF) was estimated by skinfold measurement, and abdominal visceral (VAT) and subcutaneous (SAT) adipose tissues were measured by ultrasonography. BE was assessed using the Binge Eating Scale (BES). The association between the continuous BES score (BE severity) and adiposity was assessed in the whole sample after adjustment for BMI and other confounders. The effect of BE status on adiposity was also assessed by matching binge eaters (BES ≥ 18), for sex, age, and BMI, with non-binge eaters (BES < 18). Results: We found that 17.7% of the participants were binge eaters. Continuous BES score was associated with increasing WC (0.03 cm, 95% confidence interval [CI], 0.02 to 0.05 every 1 BES unit, p < 0.001) and decreasing BF (0.01%, 95% CI, −0.02 to −0.00 every 1 BES unit, p = 0.003). No association was found between BE severity and VAT and SAT. After matching, the BF of binge eaters was 0.29% (95% CI, −0.50 to −0.07, p = 0.01) lower than that of non-binge eaters. Conclusions: Given the very small effect size, BE severity and status are not associated in a biologically meaningful manner with BF content and distribution.